Housing Policy For Indonesia: Market Enabling or Community Enabling? - Setiawan, B. (Center for Research and Community Services ITB, 2001)
This article questions the unclear policy direction and development program of urban housing in Indonesia and suggests some basic changes. The main message of this article is that housing development program in Indonesia should emphasize on creating a condition that enables the community to build their own houses (community enabling). A policy that is totally market oriented and emphasizes on economic efficiency (market enabling) is not abandoned, bus should be develop without sacrificing the aspect of social justice.